POTENSI SENYAWA DERIVAT 2-AMINOIMIDAZOLE SEBAGAI AGEN AJUVAN TERHADAP INFEKSI MULTIDRUG-RESISTANT ACINETOBACTER BAUMANNII MELALUI SIFAT ANTIBIOFILM DAN RESENSITISASI ANTIBIOTIK - Grady Krisandi; Aditya Parawangsa (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: Antibiotic resistance in hospital-acquired infection (HAI) is a big problem for healthcare. It becomes worse by the trend of antibiotic resistance that is more common in gram-negative bacteria. Acinetobacter baumannii is a gram-negative bacteria that causes HAI and is considered multidrug-resistant. This trend raises the need for an agent to resensitize antibiotics. 2-aminoimidazole found in sea sponges Leucetta and Clathrina and rich in Indonesian seas is a potential agent to resensitize antibiotics in A. baumannii. Methods: Literature searching worked using specific keywords in the search engine (Google and Google Scholar) and online databases (PubMed and SCOPUS). Twenty-three studies from various journals were retrieved. Discussion: 2-AI has various derivative compounds followed by pharmacophores. 2-Aminoimidazole triazole (2-AIT) is one of the potential derivates with antibiofilm character to resensitize Acinetobacter baumannii. Optimization of the tail group 2-AIT carries out by several methods such as simple organic chemical reactions and Suzuki-Miyaura cross-coupling. The optimized group works as an antibiofilm by binding to the bfmR protein, which plays a role in forming biofilms. The toxicity of this compound in the hemolysis test and C. elegans is relatively low. Conclusion: 2-AI has an antibiofilm activity that allows antibiotic diffusion in A. baumannii blocked by biofilm. This activity enables the resensitization of A. baumannii towards antibiotics. The safety of 2-AI has also been proven in vitro and in vivo. These findings conclude that 2-AI that extracted in sea sponges from Indonesian seas can be an agent to resensitize antibiotics in multidrug-resistant A. baumannii.